Perlindungan Hukum Bagi Pihak Yang Meminjamkan Dan Yang Meminjam Dalam Perjanjian Pinjam Pakai - Siti Hotimatul Husna (JOURNAL SAINS STUDENT RESEARCH, 2023)
Loan agreements are an important aspect of everyday life, facilitating the borrowing of goods or property for a certain period of time. In this context, legal protection for lending and borrowing parties is crucial. This paper discusses the theoretical and practical aspects of lending and use agreements as well as research methodology in evaluating the effectiveness of existing regulations. The study highlights the challenges and need to balance the rights and obligations of both parties. Referring to the Civil Code, this study examines the rights, obligations, and legal protection of both lenders and loan recipients. Equipped with car loan case studies, this paper highlights the need for clear regulations, including item identification, insurance, time limits, and rights and responsibilities that must be set out in detail in the agreement. With a deep understanding of laws and regulations, lending and use agreements can provide maximum protection for all parties involved.